Training for speed, agility, and quickness - Brown, Lee E. 1956-; Ferrigno, Vance 1961- (Human Kinetics, 2015)
Today's athletes are bigger, stronger, faster and more agile than ever before. This total training package, offers exclusive online access to a video library of the most effective drills and exercises for developing movement skills and readers can see how to perform key tests and execute the best and most complex drills from the book.